2023
DOI: 10.3892/mco.2023.2662
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors in renal cell carcinoma: A single‑center study

Abstract: Renal cell carcinoma (RCC) is a heterogeneous and complex disease with numerous pathophysiologic variants. ~40% of patients succumb due to the progression of the disease, making RCC the most fatal of the common urologic malignancies. Prognostic factors are indicators of the progression of the disease, and the precise determination of these factors is important for evaluating and managing RCC. In the present study, it was aimed to determine and find associations among the histopathological features of RCCs and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 41 publications
(66 reference statements)
0
1
0
Order By: Relevance
“…Regarding it, the studies are contradictory regarding the prognosis. Some studies consider only grade 4 as a risk factor, others have observed differences between low grades (1 and 2) and high grades (3 and 4), and in clear cell renal carcinoma differences have been observed between grades 2, 3, and 4 [95][96][97]. We observed statistically significant differences in terms of patient survival only between high grade (3 and 4) and low grade (1 and 2).…”
Section: Discussionmentioning
confidence: 40%
“…Regarding it, the studies are contradictory regarding the prognosis. Some studies consider only grade 4 as a risk factor, others have observed differences between low grades (1 and 2) and high grades (3 and 4), and in clear cell renal carcinoma differences have been observed between grades 2, 3, and 4 [95][96][97]. We observed statistically significant differences in terms of patient survival only between high grade (3 and 4) and low grade (1 and 2).…”
Section: Discussionmentioning
confidence: 40%